Electrospinning engineering of gas electrodes for high‐performance lithium–gas batteries - Jingzhao Wang; Xin Chen; Jianan Wang; Xiangming Cui; Ze Wang; Guangpeng Zhang; Wei Lyu; Maxim Shkunov; S. Ravi P. Silva; Yaozu Liao; Kai Yang; Wei Yan (Carbon Energy)
Abstract Lithium–gas batteries (LGBs) have garnered significant attention due to their impressive high‐energy densities and unique gas conversion capability. Nevertheless, the practical application of LGBs faces substantial challenges, including sluggish gas conversion kinetics inducing in low‐rate performance and high overpotential, along with limited electrochemical reversibility leading to poor cycle life. The imperative task is to develop gas electrodes with remarkable catalytic activity, abundant active sites, and exceptional electrochemical stability. Electrospinning, a versatile and well‐established technique for fabricating fibrous nanomaterials, has been extensively explored in LGB applications. In this work, we emphasize the critical structure–property for ideal gas electrodes and summarize the advancement of employing electrospun nanofibers (NFs) for performance enhancement in LGBs. Beyond elucidating the fundamental principles of LGBs and the electrospinning technique, we focus on the systematic design of electrospun NF‐based gas electrodes regarding optimal structural fabrication, catalyst handling and activation, and catalytic site optimization, as well as considerations for large‐scale implementation. The demonstrated principles and regulations for electrode design are expected to inspire broad applications in catalyst‐based energy applications.